Introduction to foliations and Lie groupoids - Moerdijk, Ieke (Cambridge studies in advanced mathematics ;, 2003)
This book gives a quick introduction to the theory of foliations and Lie groupoids. It is based on the authors' extensive teaching experience and contains numerous examples and exercises making it ideal either for independent study or as the basis of a graduate course.